Elevational changes in the avian community of a Mesoamerican cloud forest park. (2nd September 2018) - Neate‐Clegg, Montague H. C.; Jones, Samuel E. I.; Burdekin, Oliver; Jocque, Merlijn; Şekercioğlu, Çağan Hakkı
Abstract: Harboring many range‐restricted and specialized species, high elevation tropical cloud forests are diverse habitats represented in many protected areas. Despite this, many such areas receive little practical protection from deforestation and land conversion. Moreover, montane species may be more sensitive to climate change owing to various factors affecting community assembly across elevational gradients. Few studies have used annual monitoring to assess how biological communities in cloud forests may be shifting in response to habitat or climate change or assessed the efficacy of protected areas in buffering these effects. We analyzed avifaunal community trends in a 10‐yr dataset of constant‐effort bird point‐count data in a cloud forest national park in Honduras, Central America. We found that species richness and diversity increased at higher elevations, but decreased at lower elevations. Abundances of most dietary and forest‐dependency groups exhibited similar trends, and many key cloud forest species shifted upslope and/or increased in abundance. Taken together, our results suggest that the avian community is moving upslope and species composition is changing. Results for species richness and diversity were similar when only nondegraded transects were considered, suggesting the role of climate change as an important driver. At lower elevations, however, many species may be negatively affected by increased habitat degradation, favoring species with low forest dependency. Continued habitat conversion and climate change could push the cloud forest bird community further upslope, potentially resulting in increased competition, mortality, and even extirpation of some species. Increased protection is unlikely to mitigate the effects of climate change.